The Fourth Industrial Revolution: Opportunities and Challenges to the Future of Mechanical Engineering - Mbamba, Ulingeta O. L. (Tanzania Journal of Engineering and Technology, 2025)
This paper provides a conceptual overview of the developments of the Fourth Industrial Revolution (4IR) and derives challenges and opportunities for the future of the mechanical engineering profession. The paper broadly defines 4IR as the fusion of technologies and interaction across physical, digital and biological aspects, while defining mechanical engineering as "a multi-faceted discipline that encompasses the teaching, practice and guidance of others in the development and application of scientific principles to mechanical systems". The paper looks specifically at developments in the Internet of Things (IoT), blockchain technology, robotics, Big Data analytics, biotechnology, nanotechnology, 3D printing and artificial intelligence and their impact on mechanical engineering. It will also explain the impact of 4IR and emerging fields such as electronic vehicles, mechatronics and others. The aim is to show that the world is in the age of 4IR, the impact of which will be felt in all professions, although the scale in general and the scope of mechanical engineering in particular cannot yet be properly assessed. The paper concludes by stating that the world is in the 4IR era, the impact of which will be felt in all professions and the future extent of which cannot be accurately estimated. The paper ends with a recommendation on the importance of mechatronics and soft skills.